Special analyses : budget of the United States government fiscal year, 1984 (Washington, D.C. : Executive Office of the President, Office of Management and Budget, 1984)
Budget of the United States Government, 1984 contains the Budget message of the President and presents an overview of the President's budget proposals.
rpm 24/01/2019
Ref
Keywords: Budget; United States